ANALISIS LAJU RESPIRASI BUAH TOMAT (Lycopersicum esculentum MILL) TERLAPISI LARUTAN KITOSAN DENGAN VARIASI KONSENTRASI ADITIF - , WILLY D H HUTAPEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tomatoes is a horticulture product who was easy to get damage from postharvest because still doing a respiration. Respiration process will degrade the substance component so if the respiration rate getting big it will make the damage to substance faster. The method to slow down the respiration rate of horticulture product is coating the substance with edible film. The goal of this research is doing the analyze of respiration rate of tomatoes which was coated by chitosan in various concentration with determine the respiration parameters (Vmo, Kmo, Kio, Vmc, Kmc, dan Kic). In this research, tomatoes is dipped into chitosan solution which was get the additive substance in 3 variant concentration and wait until dried. Then the tomatoes and wipe are measured and get into respirator. Respirator closed and respiration proses was observed every 5 minute. If the observation of respiration process was done the tomatoes and wipe were measured again. The respiration data then use to determine the value of respiration parameters with michaelis menten equation in uncompetitive inhibition. The result showed that the treatment (coating I, coating II, coating III) isnât affect the respiration parameters value too much then the shelf life of tomatoes who was get from it be not much different which is for the single tomatoes, the shelf life of control tomatoes range from 19,6 â 34,45 hours, coating I tomatoes range from 13,2 â 50,1 hours, coating II range from 18,25 â 63,55 hours, and coating III range from 14,8 â 40,25 hours. For the group tomatoes, the shelf life of control tomatoes range from 16,05 â 44,8 hours, coating I tomatoes range from 19,45 â 27,45 hours, coating II range from 15,55 â 33,8 hours, and coating III range from 22,6 â 24,1 hours. That thing happen maybe because the age of tomatoes isnât same whereas to make the same age the tomatoes must be observe from the tomatoes planted.